(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effects of training, competence, and career development on the performance of Generation Z employees in Bima City. This research employed an associative quantitative approach with a survey method. Data were collected through questionnaires distributed to 96 Generation Z employees selected using the Lemeshow sampling formula. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The results indicate that training does not have a significant effect on employee performance. In contrast, competence and career development have positive and significant effects on employee performance. Simultaneously, training, competence, and career development significantly influence Generation Z employee performance. The coefficient of determination shows that 58.1% of employee performance variation can be explained by these three variables. The findings suggest that competence and career development are key factors in improving the performance of Generation Z employees. Therefore, organizations are encouraged to strengthen competency development programs and provide clear career pathways to optimize employee performance